Information seeking in the context of cigarette smoking: predictors from the Comprehensive Model of Information Seeking (CMIS). Issue 10 (25th November 2020) - Xiao, Zhiwen; Lee, Jaesub; Zeng, Li; Ni, Lan
ABSTRACT: Background : The CMIS indicates that key variables in actively obtaining information on cigarette smoking are demographics, direct experience, salience, and beliefs, which affects subsequent evaluations and utility of information. Method : Cross-sectional data were drawn from the HINTS-FDA 2015 national survey in which a stratified random sample of the U.S. postal addresses (N = 3, 738) self-administered a mailed paper questionnaire. Path analysis was conducted to test the CMIS. Results : Age, income, education, sexual orientation, beliefs about behavior change, and salience are significant predictors of perceived utility of information.Direct predictors of information seeking on health effects are comprehension of information (β = .06, 95% CI: .02-.09, p < .05), trust in information sources (β = .23, 95% CI: .18-.276, p < .01), and confidence in obtaining information (β = .10, 95% CI: .047-.160, p < .05). The final model produced fit indices of c 2  = 356.48, df = 24, CFI = .91, RMSEA = .061 (95% CI: .055-.067), R 2  = .098. Conclusions : The CMIS is a valid theoretical framework in predicting information seeking on cigarette smoking. This study closes a gap in the literature by addressing key factors simultaneously that influence information seeking on health effects and cessation of cigarette smoking.